(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
“Myiasis” is a parasitic infestation of live human or vertebrate animal tissues or cavities caused by dipterous larvae (maggots) which feed on the host’s dead or living tissue, liquid body substances or ingested food. The case is reported, probably the first in Bangladesh, tracheostomy myiasis. It was caused by infestation with larvae. The patient had undergone tracheostomy 3 years earlier and was a case of ca-larynx. The condition was treated by applying halothane to the tracheostomy wound, which caused spontaneous exit of approximately 30 larvae, easily removed with forceps. Predisposing factors could be: 1. Immuno-compromization due to post-irradiation state of patient; 2. Poor hygiene of tracheostomy tube; 3. Bad smell of wound, which attracts flies; 4. Living in a rural area deprived from necessary health care. Although this is not a lethal disorder, knowledge of the disease is necessary from the preventive, diagnostic and curative standpoint. It is important to proceed with identification of the larvae, distinguishing them from other types of myiasis involving different therapeutic implications. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 119-121